Optimal diagnostic thresholds for diagnosis of orthostatic hypotension with a 'sit-to-stand test'. Issue 5 (May 2017) - Shaw, Brett H.; Garland, Emily M.; Black, Bonnie K.; Paranjape, Sachin Y.; Shibao, Cyndya A.; Okamoto, Luis E.; Gamboa, Alfredo; Diedrich, André; Plummer, W. Dale; Dupont, William D.; Biaggioni, Italo; Robertson, David; et al.
Abstract : Objective: This study aimed to identify optimal blood pressure cut-offs to diagnose orthostatic hypotension during a sit-to-stand manoeuvre. Methods: This was a cross-sectional study of patients and healthy controls from the Vanderbilt Autonomic Dysfunction Center. Blood pressure was measured while supine, seated and standing. Blood pressure changes were calculated from supine-to-standing and seated-to-standing. Orthostatic hypotension was diagnosed on the basis of a supine-to-standing SBP drop at least 20 mmHg or a DBP drop at least 10 mmHg. Receiver operator characteristic (ROC) curves identified optimal sit-to-stand cut-offs. Results: Amongst the 831 individuals, more had systolic orthostatic hypotension [ n = 354 (43%)] than diastolic orthostatic hypotension [ n = 305 (37%)] during lying-to-standing. The ROC curves had good characteristics [SBP area under curve = 0.916 (95% confidence interval: 0.896–0.936), P < 0.001; DBP area under curve = 0.930 (95% confidence interval: 0.909–0.950), P < 0.001]. A sit-to stand SBP drop at least 15 mmHg had optimal test characteristics (sensitivity = 80.2%; specificity = 88.9%; positive predictive value = 84.2%; negative predictive value = 85.8%), as did a DBP drop at least 7 mmHg (sensitivity = 87.2%; specificity = 87.2%; positive predictive value = 80.1%; negative predictive value = 92.0%). Conclusions: A sit-to-stand manoeuvre with lower diagnostic cut-offs for orthostatic hypotension provides a simple screening test for orthostatic hypotension in situations wherein a supine-to-standing manoeuvre cannot be easily performed. Our analysis suggests that a SBP drop at least 15 mmHg or a DBP drop at least 7 mmHg best optimizes sensitivity and specificity of this sit-to-stand test.